The destructive effect of human stupidity: a revision of Cipolla’s fundamental laws - Barcenas, Donny R.; Kuperman, Joel; Kuperman, Marcelo Nestor (Springer, 2020)
Fil: Barcenas, Donny R. Comisión Nacional de Energía Atómica. Instituto Balseiro; Universidad Nacional de Cuyo, Argentina; Consejo Nacional de Investigaciones Científicas y Técnicas, Argentina